Simultaneous amplitude and phase contrast imaging of burning fuel particle and flame with digital inline holography: Model and verification. (September 2017) - Wu, Yingchun; Brunel, Marc; Li, Renxian; Lan, Lijuan; Ao, Wen; Chen, Jia; Wu, Xuecheng; Gréhan, Gérard
Highlights: Digital inline holography is applied to measure burning fuel particle with flame. Three models on holography of burning fuel particle are developed. Formation of amplitude and phase contrast images of particle with flame is revealed. Graphical abstract: Abstract: Three-dimensional (3D) quantitative measurements of reacting multiphase micro-objects are of great interest in fuel particle combustion, which is composed of an inner fuel particle and an outer gas flame. Three models of digital inline holography of this composite fuel particle in the framework of light scattering and diffraction theories have been proposed, and then verified with reported experimental observations. Results show that the dispersed fuel particle and the gas flame distinguish in the reconstructed amplitude and phase contrast images, and reveal that the low extinction efficiency and phase shifting of the highly transparent, weakly scattering gas flame accounts for the difference.